ANALISIS YURIDIS TERHADAP TINDAK PIDANA KEPEMILIKAN SENJATA TAJAM TANPA HAK OLEH ANAK: JURIDICAL ANALYSIS OF CRIMINAL ACTS OF OWNERSHIP OF SHARP WEAPONS WITHOUT RIGHTS BY CHILD - Hardiyanti, Hardiyanti (Faculty Of Law Bosowa University, 2022)
This research aims to determine the application of Article 2 paragraph (1) of the Emergency Law No. 12 Year 1951 against the criminal act of possession without the right of a sharp weapon by the child and to find out the criminal sanctions imposed in the criminal case decision No. 6/Pid.Sus-Anak/2020/PN.Mks. is in accordance with the aspects of child criminalization. The results showed that “the Application of Article 2 paragraph (1) Emergency Law No. 12 Year 1951 on the Crime of Control without the Right to Sharp Weapons by Children is appropriate, because Akbar Bin Rudi (a child who is in conflict with the law) has fulfilled all of these elements, namely (1) the element of Whoever; element (2) without the right to enter into Indonesia, makes, receives, tries to obtain it, delivers or tries to surrender, control, carry, have inventory in it or have in his possession, keep, transport, hide, use or leave Indonesia; and (3) elements of a weapon, a stabbing weapon, or a stabbing weapon (slag steek of stootwapen). Seeing that all these elements are fulfilled, there is no attempt for Akbar Bin Rudi to escape from the criminal responsibility he was accused of. Likewise, from the side of the public prosecutor, it is not possible to carry out SKP2 (the Decree on the Termination of Prosecution). However, the public prosecutor should be obliged to seek diversion by considering the age of Akbar Bin Rudi's child. Criminal Sanctions Imposed in the Decision on Criminal Case No. 6/Pid.Sus-Anak/2020/ PN.Mks. is imprisonment for 5 (five) months in LPKA Maros for Akbar Bin Rudi (a child who is in conflict with the law), although the sentence is quite light when compared to the penalty stipulated in the relevant legislation, but in a criminal case carrying a sharp weapon without permission done by Akbar Bin Rudi, here the author does not agree with what was decided by Rusdiyanto Loleh, SH, MH (Child Judge) at the Makassar District Court in Decision Number: 6/ Pid.Sus-Anak/2020/PN.Mks. The judge should have been obliged to seek diversion first. This refers to Article 81 paragraph (2) of Law of the Republic of Indonesia Number 11 Year 2012 concerning the Criminal Justice System for Children and Regulation of the Supreme Court of the Republic of Indonesia Number 4 Year 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System”.